PENGGUNAAN METODE PROFILE MATCHING UNTUK SISTEM PENUNJANG KEPUTUSAN KENAIKAN JABATAN PADA INSTANSI PEMERINTAH - Frieyadie Frieyadie (Paradigma, 2016)
Findings problems are detected, such as: Still the ratings unilaterally cause social jealousy and judgment becomes objective. There is still no effective assessment make judgments solely based on certain criteria. The purpose of this study is to: Build a decision support system that can help the relevant agencies to provide recommendations for decision-making and judgment in determining which employees will be promoted later to be given the post. Improving the quality of research, thereby reducing errors in melolosakan prospective employees that are not in accordance with the standards of quality positions at the agency. Profile Matching methods used to solve problems in this study. The results of the calculation Profile Matching stated that the alternative selected and the most appropriate criteria are employee-2 (P2) with the results Profile Matching stated that the alternative selected and the most appropriate criteria are employee-5 (P5) with the results Profile Matching obtained of the questionnaire by the three respondents gave the answer can be calculated and the final result that the employee-5 (P5) of 4.15 compared with employees excel-1 (P1) of 4.06, an employee-4 (P4) with a value of 4.02, employee-3 (P3) of 3.88, and an employee-2 (P2) of 3.85Keywords: Metode Profile Matching, Decision Support System, The increase Position